The effects of fınancıal pressure polıcıes on economıc growth: The case of OECD countries - Nar, Mehmet (Technological and Economic Development of Economy, 2025)
In this study, the effects on economic growth of financial pressure policies applied in OECD countries are examined. For this purpose, the “financial pressure index (FPI)” was calculated by using 10- year data for 2010–2020 from 37 OECD countries and “growth rates” were obtained. The FPI was calculated using (i) loans extended to the pri¬vate sector, (ii) loans extended to the central government, (iii) interest payments and (iv) inflation rate data. In calculating FPI, first of all, the data was standardized. Following the standardization process, the data was weighted using Principal Component Analysis (PCA) to calculate the FPI. After weighting the data, each standardized value was aggregated by multiplying it by its own weighted value, and the final FPI was ultimately calculated. Economic growth rates were calculated as a percentage of GDP. Finally, the analysis was carried out by comparing the calculated FPI with the economic growth rates. According to the results of the analysis, the coefficient of FPI was statistically significant (p < 0.05). In this context, every 1-point increase in FPI reduced GDP by 0.178 points. First published online 17 September 2024